2019
DOI: 10.3390/drones3030067
|View full text |Cite
|
Sign up to set email alerts
|

Improving Intertidal Reef Mapping Using UAV Surface, Red Edge, and Near-Infrared Data

Abstract: Coastal living reefs provide considerable services from tropical to temperate systems. Threatened by global ocean-climate and local anthropogenic changes, reefs require spatially explicit management at the submeter scale, where socioecological processes occur. Drone surveys have adequately addressed these requirements with red-green-blue (RGB) orthomosaics and digital surface models (DSMs). The use of ancillary spectral bands has the potential to increase the mapping of all reefscapes that emerge during low ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 25 publications
2
26
0
Order By: Relevance
“…Spatial patterns emerging from ecological status classification, also display a barrier reef on sand with a vigorous seaward front core, while the retrograded and sparse reefs are mainly located in the south-east part and next to shoreline. This seems to be consistent with previous work carried out by Collin et al (2019) that have described a strong polarization of S. alveolata reefs with high abundance on forereef and low abundance on backreef. The forereef is subject to strong hydrodynamic and potentially higher coarse sediment resuspension, leading to increased tube-building activity, while the back reef mainly expands into more sheltered and muddier environments, less favorable to S. alveolata development (Bonnot-Courtois et al, 2008).…”
Section: Contribution Of Hyperspectral and Lidar Combination To Reef supporting
confidence: 93%
See 2 more Smart Citations
“…Spatial patterns emerging from ecological status classification, also display a barrier reef on sand with a vigorous seaward front core, while the retrograded and sparse reefs are mainly located in the south-east part and next to shoreline. This seems to be consistent with previous work carried out by Collin et al (2019) that have described a strong polarization of S. alveolata reefs with high abundance on forereef and low abundance on backreef. The forereef is subject to strong hydrodynamic and potentially higher coarse sediment resuspension, leading to increased tube-building activity, while the back reef mainly expands into more sheltered and muddier environments, less favorable to S. alveolata development (Bonnot-Courtois et al, 2008).…”
Section: Contribution Of Hyperspectral and Lidar Combination To Reef supporting
confidence: 93%
“…Obtained results also reinforce the recommendations encouraging integration of direct observation field techniques with remotely sensed data to capture detailed habitat information at large scales, thus avoiding trade-offs between three types of scale: spatial, temporal and thematic (Lecours et al, 2015;Rhodes et al, 2015;D'Urban et al, 2020). The benthic habitat map of Champeaux obtained from the hyperspectral airborne imagery using Mahalanobis supervised classification allows the delineation of a higher number of discriminated habitats (ten) than what was identified using RGB (Red-Green-Blue) images and digital surface model, as shown for S. alveolata reefs growing atop of soft sediment exclusively (Collin et al, 2019). The most significant information that the pattern of class distribution reveals is the distinction between two types of S. alveolata formations; large reefs developing on sandy bottoms and smaller veneers encrusting rocky shore areas.…”
Section: Coherence Of Benthic Feature Distributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the central areas of forests should provide optimal material to build a global map of giant kelp. (c) The use of Unmanned Aerial Vehicles (UAV) for coastal habitat mapping is a simple, cost-effective and reliable technology [39] that has been successfully used to map and validate intertidal biogenic reefs [40], saltmarsh biomass [41], and algal blooms [42]. Recent surveys to detect macroalgae in temperate coastlines have shown that RGB (additive primary colors-red, green, and blue-model) and multispectral cameras mounted on UAVs produce accurate imagery able to detect water turbidity and a range of taxonomical groups of algae in surface or shallow water, with the exception of spectrally similar species [18,43].…”
Section: Introductionmentioning
confidence: 99%
“…The use of drone technology for the imagery acquisition and for the generation of digital surface models (DSMs), using structure from motion (SfM) photogrammetry [15], is of many interests, especially for the coastal monitoring [16]. It allows for creating orthophotomosaics and DSMs at VHSR and very high temporal resolution (VHTR) [17].…”
Section: Introductionmentioning
confidence: 99%